Analisa Nilai R/C pada Usaha Tani Padi di Desa Pahesan Kecamatan Godong Kabupaten Grobogan Jawa Tengah - Muslikun, Muslikun; Subantoro, Renan; Fachriyan, Hilmi Arija; Ni’mah, Lu’lu’a Ulyn (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Rice (Oryza sativa L.) farming with a planting system using a transplanter machine in Pahesan Village, Godong District, Grobogan Regency, Central Java has been analyzed using the Revenue Cost Ratio approach which produces a value of 1.9. This value shows that the farming business is feasible and profitable. The overall results of this research indicate that rice cultivation using a transplanter system in Pahesan Village provides significant benefits, where the income obtained is much greater than the production costs incurred. Apart from that, the use of transplanters also contributes to labor efficiency and increases productivity, thereby supporting the sustainability of farming in the Pahesan Village area, Godong District, Grobogan Regency, Central Java, which is very profitable and has the potential to improve farmers' welfare through efficiency and increasing rice production yields.